Money, interest and prices - Patinkin, Don (New York, 1956)
This work is the outgrowth of ideas first presented in a doctoral dis sertation submitted to the University of Chicago in 1947 and then further developed in a series of articles published in various journals and anthologies through the years 1948 to 1954. The reader interested in consulting these articles will find them listed in the Bibliography at the end of the book. The book itself, however, makes but few explicit references to them. Correspondingly, it makes practically no attempt to show how its argument is specifically related to that of these earlier articles. It must also be emphasized that, with the exception of a few pages, the actual exposition of this book is entirely new. It represents an extensive reworking, elaboration, and refinement of the basic ideas of these articles within a much more systematic and comprehensive framework than was was originally achieved. Furthermore and most has been able to dispenset gratifyingly-the text of the present book to dispense with the apparently forbidding mathematical apparatus which marked the first of these articles. The argument is instead developed by the use of the more familiar literary and graphical techniques of modern economic analysis. The nature of the argument of this book has made it necessary to use numerous internal cross-references. These are of two types. First, there are those to the Mathematical Appendix and Supplementary Notes. Their purpose is to indicate to the reader the nature of the additional information that he can find in these places should he be interested in consulting them. Second, there are the cross-references to the text itself. Their main purpose is to remind the reader where if need be-he can refresh his memory about an earlier conclusion which is being used as the basis for a further development in the argu ment. The reader who has no need for these reminders and who is interested only in the text itself can therefore ignore all cross-references and proceed with his reading undisturbed. On the other hand, anyone who wishes to follow up these references will find his task simplified by the fact that each page of this book carries the appropriate chapter section number (in the case of the text), appendix-section number (in the case of the Mathematical Appendix), or note-section number (in the case of the Supplementary Notes).
Keywords: Money